Dinâmica espacial do consumo de água: uma análise das influências socioeconômicas e dos impactos da pandemia de Covid-19 - Lopes, Tereza Margarida Xavier de Melo (2024)
To ensure equitable access to water, it is imperative to analyze the dynamics of cities through spatial statistics. This dynamics reveals heterogeneous consumption patterns that are directly influenced by socioeconomic factors. Therefore, this study recognizes that cities should not be approached as homogeneous study entities but as multivariate systems, highlighting intra-city spatial disparities. In this context, Brazil, a country of continental scale, exhibits significant disparities in both water consumption and socioeconomic factors. Given this, the present study aims to assess the configuration of inter-municipal spatial patterns in Brazil and analyze the intra-municipal scenario of a major urban center: the city of Fortaleza-CE. Thus, correlations between consumption and per capita income will be quantified, as well as the transformations in water demand in the face of an extreme event: the COVID-19 pandemic. Accordingly, this study initially applied two spatial statistical tests: the Global Moran's Index (I) and the Local Indicator of Spatial Association (LISA). It was observed that, both at the national and municipal levels, the spatial distribution of water consumption does not occur uniformly, highlighting the formation of clusters with higher consumption rates in regions with higher income and, conversely, in regions with lower incomes. Thus, the study reveals a strong spatial autocorrelation between water consumption and per capita income, at both national and municipal scales, emphasizing water and socioeconomic inequalities in Brazil and, particularly, in the city of Fortaleza. Subsequently, the influences of different phases of the COVID-19 pandemic on Fortaleza's consumption types (residential, commercial, industrial, public, and mixed) were observed. The results indicate a significant impact of the pandemic, particularly on residential and commercial consumptions in Fortaleza, suggesting a high susceptibility of water supply systems to changes in population habits. Therefore, this study contributes to a deeper understanding of the complex dynamics shaping water consumption in Brazil and provides a fundamental basis for the development of water policies aimed at ensuring equitable access.